Producción científica mundial en albendazol: un estudio bibliométrico - Granados-Álvarez, Santiago; Marín-Rincón, Hamilton; Ramírez-Jaramillo, Valeria; Sánchez-Carmona, Daniel; Bedoya-Arias, Juan E; Rodriguez-Morales, Alfonso J; Machado-Alba, Jorge Enrique (Revista Médica de Risaralda, 2015)
Producción